2017
DOI: 10.1039/c6ra25128e
|View full text |Cite
|
Sign up to set email alerts
|

Electrical anisotropy and multidimensional pressure sensor of aligned Fe3O4@silver nanowire/polyaniline composite films under an extremely low magnetic field

Abstract: The PDMS sealed aligned Ag nanowire/PANI composite film as a multi-dimensional pressure sensor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 58 publications
(75 reference statements)
0
9
0
Order By: Relevance
“…The length range of the reported AgNWs is from 0.5 mm to 31.2 mm, which are summarized in Table 1. 6,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Some reports have proved that the performance of the AgNWs relies mainly on the nanowire structure, such as diameter, length, dispersity, and so on. 24,25 More importantly, the lengths of AgNWs are key elements for forming the high transmittance with a low haze, and low sheet conductivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The length range of the reported AgNWs is from 0.5 mm to 31.2 mm, which are summarized in Table 1. 6,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Some reports have proved that the performance of the AgNWs relies mainly on the nanowire structure, such as diameter, length, dispersity, and so on. 24,25 More importantly, the lengths of AgNWs are key elements for forming the high transmittance with a low haze, and low sheet conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Fang et al 22 have experimentally shown that the AgNWs were prepared via a solvothermal method, but the nanowires were below 30 mm. Liu et al 23 have prepared AgNWs using this approach, with length ranging from 5-10 mm.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of magnetic-controlled nanoparticles with nano morphological tunings facilitates the formation of aligned silver nanostructures-PANI composite films. Interestingly, the resistive response contrastively provides the sensory outputs with respect to a parallel and perpendicular mode of sensing [140]. Recently, commercial sponges were carbonized into airy 3D carbon foams with thermal treatments.…”
Section: Polyaniline Sensorsmentioning
confidence: 99%
“…Therefore, it has become a popular practice to functionalize materials that exhibit low magnetic susceptibilities with superparamagnetic nanoparticles (i.e. iron oxide-based species) [13,55,56].…”
Section: Magnetically Aligned Composites With Simple 2d Structuresmentioning
confidence: 99%
“…Isotropic composites display the same properties at all directions while anisotropic composites show varying properties along different axes [11]. Anisotropic composites are of significance due to the increasing need of materials with controlled and superior thermal [12], electrical [13], mechanical [14], optical [15], barrier [16], or even selfshaping properties [17] for a wide range of applications from aerospace engineering to medicine [3].…”
Section: Introductionmentioning
confidence: 99%